Canonical texts in the audiovisual context: surtitling Eugene Onegin for Polish audiences. - Rędzioch-Korkuz, Anna (Perspectives: Studies in Translatology, 2021)
The article aims to discuss Polish surtitles for the opera Eugene Onegin by Pyotr Tchaikovsky staged at the Polish National Opera in Warsaw. The point of departure is the question of power of the original and its translations seen as a constraining factor. It attempts to assess whether the canonical nature of the original source may be considered another constraint in the surtitling process along with the power of creative authors responsible for the staging. To this end, it presents a comparative analysis of three Polish translations of two arias, i.e. Letter Aria and Lensky's Aria, which help to determine how similar they are in terms of style, form and content, and which is subsequently followed with a multimodal analysis of the surtitles provided for the arias. It turned out that one of the translations served as the textual basis of the surtitles with a relatively high degree of correspondence. The literary status of this translation had a direct bearing on the shape of the surtitles, which did not cater for the semiotic integrity of the performance. As such, the power of the intermediary text should be considered another significant constraint in the process of surtitling.